Novel pore-filling membrane based on block sulfonated poly (ether sulphone) with enhanced proton conductivity and methanol resistance for direct methanol fuel cells. (1st June 2019) - Zhang, Chongyang; Yue, Xigui; Mu, Yongfeng; Zuo, Xiaodan; Lu, Nan; Luo, Yuchao; Na, Ruiqi; Zhang, Shuling; Wang, Guibin
Abstract: The problem remains unsolved in DMFCs applications that the increase in proton conductivity is usually caused the permeation of methanol. Herein, a novel kind of pore-filling membrane is investigated to meet this challenge. The porous substrate is fabricated from block poly (ether sulphone) with low degree of sulfonation, which form well-developed conductive channels owing to an aggregation of sulfonic acid groups, ensuring low methonal crossover and swelling ratio. The pore structures are achieved by a solution casting method which introduces alpha-cyclodextrin as the porogen. The resulting porous substrate possesses homogeneous opening pore structures. Then, the filling electrolyte, an organic-soluble tetrabutylammonium 4-vinylbenzene sulfonate, is used to fill the substrate and form a crosslinked network inside the pores to ensure high proton conductivity. The pore-filling membrane with block polymers shows higher proton conductivity (0.083 S cm −1 at 80 °C) than that prepared by random polymers (0.072 S cm −1 at 80 °C). Compared with Nafion 117, the composite membrane exhibits higher dimensional stability (6.6%) and methanol resistance (4.0 × 10 −7 cm 2 s −1 ). Furthermore, the pore-filling membrane outperforms Nafion 117 with an open circuit voltage of 0.61 V as well as a maximum power density of 46.8 mW/cm 2 under 10 M methanol condition. Graphical abstract: Image 1 Highlights: Novel CSPS filled SPES pore-filling proton exchange membrane. Porous substrate based on block sulfonated copolymers enhanced proton conductivity. Significant suppression of methanol crossover over pore-filling membranes. Single cell performance outperformed Nafion 117 in 10 M methanol.